MENANAMKAN SEMANGAT PELAYANAN SEJAK DINI MELALUI PENDIDIKAN AGAMA KRISTEN - Kasingku, Juwinner; Winda Novita Warouw (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the midst of rapid technological advancement and the strong influence of consumerist culture, children today are increasingly driven to live individualistic lives and show less sensitivity toward others. This phenomenon highlights the critical role of Christian Religious Education (CRE) in instilling a spirit of service from an early age. This study aims to explain how strategies and implementations within CRE can shape a servant-hearted character in children. Using a qualitative method with a library research approach, data were collected from various relevant academic sources. The findings reveal that CRE plays a strategic role in nurturing a spirit of service through three main approaches: the early inculcation of Christian values, the use of relevant and interactive learning, and providing opportunities for children to practice serving directly. By taking Jesus as the ultimate example, children can learn to serve with love, responsibility, and humility. When these strategies are applied consistently, the spirit of service will grow naturally and shape children into individuals who are ready to serve in the family, church, and community from an early age.